2022
DOI: 10.1101/2022.01.22.22269630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breakthrough SARS-CoV-2 infections in MS patients on disease modifying therapies

Abstract: Background. Patients with Multiple Sclerosis (pwMS) treated with anti-CD20 or fingolimod showed a reduced humoral response to SARS-CoV-2 vaccines. In this study we aimed to monitor the risk of breakthrough SARS-CoV-2 infection in pwMS on different Disease Modifying Therapy (DMT). Methods. Data on number of vaccinated patients and of patients with a breakthrough infection were retrospectively collected in 27 Italian MS centers. We estimated the rate of breakthrough infections and of infection requiring hospital… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…However, in the absence of humoral immunization, it is doubted if the T-cells could provide adequate clinical protection among pwMS on aCD20 and S1PRM. The current real-world evidence confirms the predictive effect of seroconversion on post-vaccination COVID-19 incidence and severity 62 , and indicates rising comparative incidence and severity of COVID-19 among pwMS on S1PRM and aCD20 following vaccination of pwMS 62,71-73 . The less-extensive humoral blunts in pwMS on TERI – and possibly ALEM – do not seem to have had any significant effect on vaccine effectiveness.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…However, in the absence of humoral immunization, it is doubted if the T-cells could provide adequate clinical protection among pwMS on aCD20 and S1PRM. The current real-world evidence confirms the predictive effect of seroconversion on post-vaccination COVID-19 incidence and severity 62 , and indicates rising comparative incidence and severity of COVID-19 among pwMS on S1PRM and aCD20 following vaccination of pwMS 62,71-73 . The less-extensive humoral blunts in pwMS on TERI – and possibly ALEM – do not seem to have had any significant effect on vaccine effectiveness.…”
Section: Resultssupporting
confidence: 69%
“…The less-extensive humoral blunts in pwMS on TERI – and possibly ALEM – do not seem to have had any significant effect on vaccine effectiveness. Regarding the protective effect of T-cell responses, currently, the only clue lies within the Etemadifar et al 72 study – although not confirmed by a larger study 73 ; it showed that among the vaccinated pwMS, the ones on aCD20 experienced lower incidence and severity of COVID-19 in comparison with those on fingolimod. The former are known to be prone to worse COVID-19 outcomes 64 but show robust post-vaccination T-cell responses, while the latter do not develop proper T-cell immunization following vaccination.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, CMI in anti-CD20-treated patients may be diminished or at least very heterogeneous after 2 or 3 SARS-CoV-2 vaccinations, depending on patient population or comedication 4. Together with the ubiquitously reported impaired humoral responses to SARS-CoV-2 vaccines in anti-CD20-treated patients, the consequence is undoubtedly an increased risk of severe breakthrough infections in this population, as reported from two potentially overlapping study populations 28 29…”
Section: Discussionmentioning
confidence: 95%
“…In this case, the hospitalization rate was higher in ocrelizumab patients compared with fingolimod or the rest of pwMS (16.7%, 3.6% and 3.9% respectively). 21 SARS-CoV-2 vaccines have demonstrated to be safe in pwMS and other demyelinating diseases. However, some rare cases of neurological adverse events, including new diagnoses of MS, transverse myelitis, acute disseminated encephalomyelitis (ADEM) or MS relapses, are being described after all types of SARS-CoV-2 vaccines.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%